PERAN BADAN PERMUSYAWARATAN DESA DALAM PENGAWASAN PEMBANGUNAN (STUDI KASUS DI DESA KAIDUNDU, KECAMATAN BULAWA, KABUPATEN BONE BOLANGO) - Ibrahim, Farhan; Prihatini Tui, Fenti; Noho Nani, Yacob (Universitas Djuanda, 2024)
The objective of this research is to understand and describe the role of the Village Consultative Body (BPD) in construction supervision (case study in Kaidundu Village, Bulawa Subdistrict, Bone Bolango Regency) from the aspects of (a) Expectation, (b) Norm, (c) Performance, and (d) Evaluation. This research employs a descriptive approach with qualitative data analysis. The data are collected through observation, interviews, and documentation.The results indicate that the role of the Village Consultative Body in construction supervision in Kaidundu Village, Bulawa Subdistrict, Bone Bolango Regency, has been implemented in accordarice with Bone Bolango Regency Regulation Number 4 of 2017 concerning the Village Consultative Body, viewed from the aspects of expectations, norms, behavior manifestation, evaluation, and sanctions. However, several issues were still identified during its implementation. One of the main issues is the educational background of the human resources in the Village Consultative Body (BPD), which is relatively low. This is because junior high school graduates and high school equivalents still dominate the membership of the Village Consultative Body in Kaidundu Village. Additionally, the members lack training and technical guidance in Kaidundu Village, Bulawa Subdistrict, Bone Bolango Regency. This becomes a source of problems in the supervision conducted by the Village Consultative Body itself. In conclusion, the role of the Village Consultative Body in construction supervision in Kaidundu Village, Bulawa Subdistrict, Bone Bolango Regency, still needs improvement in expectations, norms, behavior manifestation, evaluation, and sanctions.